Continuous generalized Hankel-Clifford wavelet transformation - Gorty, V. R. Lakshmi (International Journal of Computer Sciences and Engineering, 2013)
In this paper, the generalized Hankel-Clifford wavelet transformation is developed. Using the developed theory of generalized Hankel-Clifford convolution, the generalized Hankel-Clifford translation is introduced. Properties of the kernel Dμαβ(x,y,z) are developed in the study. Using the properties of kernel the generalized Hankel-Clifford wavelet transformation is defined. The existence of the generalized Hankel-Clifford wavelet transformation is given by a theorem. The boundedness and inversion formula for the generalized Hankel-Clifford wavelet transformation is obtained. A basic wavelet which defines continuous generalized Hankel-Clifford wavelet transformation, its admissibility conditions and the wavelet to the function is proved. Examples have been shown to explain the studied continuous generalized Hankel-Clifford wavelet transformation. MSC: 44A20, 42C40, 46